Influencia del inbound marketing en la decisión de compra online en los emprendimientos de ropa femenina en las consumidoras menores de 30 años en Lima Metropolitana - Jauregui Verastegui, Maria del Carmen (2022)
The present investigation presents as a problem: How does inbound marketing influence the decision to buy online in consumers under 30 years of age in women's clothing enterprises in metropolitan Lima? Based on this, it is proposed how to determine how inbound marketing influences the purchase decision of consumers under 30 years of age in women's clothing businesses in metropolitan Lima. Therefore, it proposes a research with a quantitative approach, non-experimental design and basic type, based on a questionnaire of closed questions. Evidencing a relationship between the content of digital platforms, the interaction between users and customer satisfaction with decision making; given that, it is evident that the use of more than two platforms is recurrent, considering that the most preponderant is Instagram, being in turn the chosen one so that they can receive relevant information from the brands. Concluding based on this, that inbound marketing is directly related to the purchase decision of consumers under 30 years of age in women's clothing enterprises in metropolitan Lima.